An innovative and integrative assay for toxicity testing using individual fish embryos. Application to oxazepam. (August 2017) - Granger Joly de Boissel, Philippine; Gonzalez, Patrice; Buleté, Audrey; Daffe, Guillemine; Clérandeau, Christelle; Vulliet, Emmanuelle; Cachot, Jérôme
Abstract: This paper describes the development of an integrative embryo-toxicity assay in Japanese medaka allowing analysis of several toxicological endpoints together in a same individual. In this assay, embryos are topically exposed, and survival, hatching success, malformations, biometry, behaviour, and target gene expression are subsequently analysed in each individual. This assay was applied to oxazepam, an anxiolytic pharmaceutical compound currently found in wastewater treatment plant effluent. Even if oxazepam accumulation in embryos was very low, it caused spinal and cardiac malformations, delayed growth, erratic swimming and deregulation of genes involved in apoptosis, DNA repair and mitochondrial metabolism. Relationship between gene deregulation, abnormal behaviour, and developmental anomalies was demonstrated. This assay is sensitive enough to detect adverse effects at low chemical concentrations and at multiple endpoints in a unique fish embryo. This integrative embryo-toxicity assay is a powerful tool to characterize the spectrum of effects of new chemicals and also to link effects induced at different molecular, tissue and physiological levels. Graphical abstract: Highlights: Development of an integrative embryo-toxicity assay in Japanese medaka embryos. The anxiolytic pharmaceutical oxazepam was used as test compound. Survival, malformations, behaviour, and gene expression were analysed in a same individual. Oxazepam is poorly accumulated in embryos. Oxazepam induces malformations, erratic swimming and delayed growth.